IMPLEMENTASI EDUPRENEURSHIP DI MADRASAH ALIYAH (MA) ALKHAIRAAT KOTA GORONTALO - Putri Yulandari L Mangambali; Imam Mashudi (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2025)
This study examines the implementation of edupreneurship at MA Alkhairaat Kota Gorontalo, a pesantren-based madrasah aliyah facing challenges in integrating religious values with entrepreneurial education under the Merdeka Curriculum. The research aims to reveal regulatory dynamics, implementation forms, constraints, school efforts, and development recommendations through qualitative case study approach. Data collection utilized semi-structured interviews with prakarya teacher Roman Oluwa (6 years-experience), analyzed thematically from transcripts focusing on regulation coordination weaknesses, P5 program and local food bazaar implementation, non-specialist teacher issues, delayed policy information due to religious focus, limited facilities, and contextual strategies like waste wood recycling. Findings confirm edupreneurship potential through P5 and contextual mentoring despite systemic barriers, validating the hypothesis that pesantren integration enriches entrepreneurship when supported by stronger regulations and external collaboration. Conclusions highlight adaptive implementation models for madrasah, recommending pentahelix partnerships, specialist teacher training, accelerated policy dissemination, and Society 5.0-based longitudinal evaluations for sustainable micro-enterprise development